2015
DOI: 10.1186/s12870-015-0567-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of gene expression associated with tuberous root formation and development in sweetpotato (Ipomoea batatas)

Abstract: BackgroundThe tuberous root of sweetpotato is undisputedly an important organ from agronomic and biological perspectives. Little is known regarding the regulatory networks programming tuberous root formation and development.ResultsHere, as a first step toward understanding these networks, we analyzed and characterized the genome-wide transcriptional profiling and dynamics of sweetpotato root in seven distinct developmental stages using a customized microarray containing 39,724 genes. Analysis of these genes id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Differentiation of tuberous roots from adventitious roots coincides with an increase in the activity of primary cambium and a decrease in the lignification of stele (Togari, 1950). Consistent with this observation, genes involved in lignin biosynthesis are down-regulated during the initiation of tuberous root development (Firon et al, 2013;Wang et al, 2015). In addition, overexpression of Maize Lc gene in transgenic sweetpotato induced the activation of the lignin biosynthetic pathway in the developing roots, leading to pencil-type root differentiation (Wang H. et al, 2016).…”
Section: Resultsmentioning
confidence: 64%
“…Differentiation of tuberous roots from adventitious roots coincides with an increase in the activity of primary cambium and a decrease in the lignification of stele (Togari, 1950). Consistent with this observation, genes involved in lignin biosynthesis are down-regulated during the initiation of tuberous root development (Firon et al, 2013;Wang et al, 2015). In addition, overexpression of Maize Lc gene in transgenic sweetpotato induced the activation of the lignin biosynthetic pathway in the developing roots, leading to pencil-type root differentiation (Wang H. et al, 2016).…”
Section: Resultsmentioning
confidence: 64%
“…The data also indicated that the expressions of several regulatory genes involved in meristematic tissue identity and maintenance are elaborately controlled during the storage root initiation process. Wang et al (2015) also analyzed the transcriptional profiles of sweetpotato roots in seven distinct developmental stages using a microarray containing 39,724 genes, and found 5,368 genes showing significant changes in gene expression during storage root development. The results suggested that starch biosynthesis is up-regulated and lignin biosynthesis is down-regulated during storage root development, along with changes in other biological processes, as summarized in Table 1.…”
Section: Analysis Of Gene Expression Change During Storage Root Formamentioning
confidence: 99%
“…These gene expression studies also reported the changes in expression of several regulatory genes during the formation of storage roots. McGregor (2006) and Wang et al (2015) reported the differential expression of auxin-responsible genes in fibrous and storage roots. Also, McGregor (2006) and Firon et al (2013) reported the differential expression of ethylene-responsive factors.…”
Section: Analysis Of Gene Expression Change During Storage Root Formamentioning
confidence: 99%
See 2 more Smart Citations